Thienyl quinoxaline compound and preparation method thereof, polymer, electrochromic material and electrochromic device

By using thienylquinoxaline compounds to prepare polymers and form D-π-A-π-D structures, the problem of poor performance of existing electrochromic conjugated polymers is solved, and low driving voltage and high contrast are achieved and electrochromic materials with fast switching time.

CN119462699AActive Publication Date: 2025-02-18WUYI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411508321.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing electrochromic conjugated polymers have problems such as high driving voltage, low contrast, slow switching time and poor stability.

Method used

The polymer is prepared by using thienylquinoxaline compounds as monomers, and the D-π-A-π-D structure is formed, which enhances the charge transfer capacity in the molecule, reduces the initial oxidation potential of the monomer, and improves the Electrochromic properties.

Benefits of technology

The polymer is achieved with low driving voltage, high contrast, fast switching time and good stability, and the performance of electrochromic materials is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462699A_ABST
    Figure CN119462699A_ABST
Patent Text Reader

Abstract

The invention discloses a thienyl quinoxaline compound and a preparation method thereof, a polymer, an electrochromic material and an electrochromic device. The thienyl quinoxaline compound has a structural formula shown as a formula (I): # imgabs0 #, wherein R1, R2, R3 and R4 are independently selected from halogen, C1-18 alkyl, C6-20 aryl or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl; a polymer formed by polymerizing the thienyl quinoxaline compound has the advantages of low driving voltage, high contrast ratio, short switching time and good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochromic materials, and in particular to a thienylquinoxaline compound and a preparation method thereof, a polymer, an electrochromic material and an electrochromic device. Background Art

[0002] Electrochromism (EC) refers to the reversible change of color, absorbance and transmittance of a material under the action of applied voltage. Materials with this color-changing property are called electrochromic materials. Compared with other electrochromic materials, electrochromic conjugated polymers have a wide absorption spectrum (from ultraviolet to visible light, as well as absorption range in the infrared region), high optical contrast and fast switching speed, making them excellent candidates for green building smart windows, anti-glare mirrors, electronic displays, smart glasses and wearable clothing.

[0003] The electrochromic properties of conjugated polymers are a redox process involving the removal or injection of electrons (p-doping or n-doping, respectively) from the electrochromic conjugated polymer, leading to the formation of polarons and bipolarons and causing structural changes in the polymer backbone. Conventional polythiophenes generally have poor solubility and are too tricky to further process. Existing electrochromic polymers suffer from high driving voltages, low contrast, slow switching times, and poor stability.

[0004] Therefore, there is an urgent need to provide a compound monomer so that the polymer formed by polymerizing the compound monomer has low driving voltage, high contrast, fast switching time and good stability. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first aspect of the present invention provides a thienylquinoxaline compound, and the polymer formed by the thienylquinoxaline compound has the advantages of low driving voltage, high contrast, fast switching time and good stability.

[0006] The second aspect of the present invention also provides a method for preparing a thienylquinoxaline compound.

[0007] The third aspect of the present invention also provides a polymer.

[0008] The fourth aspect of the present invention also provides a method for preparing a polymer.

[0009] The fifth aspect of the present invention also provides an electrochromic material.

[0010] The sixth aspect of the present invention also provides an electrochromic device.

[0011] According to the first aspect of the present invention, a thienylquinoxaline compound is provided, which has the structural formula shown in formula (I):

[0012]

[0013] Among them, R 1 , R 2 , R 3 and R 4 independently selected from halogen, C 1~18 Alkyl, C 6~20 or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl;

[0014] X 1 and X 2 independently selected from halogen;

[0015] π is selected from thiophene or 3,4-ethylenedioxythiophene;

[0016] D is selected from thiophene or 3,4-ethylenedioxythiophene.

[0017] A thienylquinoxaline compound provided according to an embodiment of the present invention has at least the following beneficial effects:

[0018] The polymer obtained by polymerizing the thienylquinoxaline compound provided by the present invention has the advantages of low driving voltage, high contrast, fast switching time and good stability.

[0019] According to a preferred embodiment of the present invention, R 1 , R 2 , R 3 and R 4 Independently selected from C 4~15 Alkyl, C 6~20 or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl.

[0020] According to a preferred embodiment of the present invention, the thienylquinoxaline compound is selected from one of the following structural formulas:

[0021]

[0022] According to the second aspect of the present invention, the method for preparing the thienylquinoxaline compound comprises the following steps:

[0023] Under a protective gas atmosphere, the receptor, compound 1, a solvent and a catalyst are mixed to carry out a Stille coupling reaction to obtain a thienylquinoxaline compound;

[0024] The compound 1 is selected from tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane or tributyl(2-thienyl)tin;

[0025] The structural formula of the receptor is as follows:

[0026]

[0027] According to a preferred embodiment of the present invention, the mass ratio of the receptor to compound 1 is 1:(1-5).

[0028] According to a preferred embodiment of the present invention, the mass ratio of the receptor to compound 1 is 1:(1.4-4).

[0029] According to a preferred embodiment of the present invention, the mass ratio of the acceptor to the catalyst is 1:(0.03-0.0625).

[0030] According to a preferred embodiment of the present invention, the temperature of the Stille coupling reaction is 70-130°C.

[0031] According to a preferred embodiment of the present invention, the temperature of the Stille coupling reaction is 90-120°C.

[0032] According to a preferred embodiment of the present invention, the Stille coupling reaction time is 8-24 hours.

[0033] According to a preferred embodiment of the present invention, the Stille coupling reaction time is 12-24 hours.

[0034] According to a preferred embodiment of the present invention, the catalyst comprises Pd(PPh 3 ) 4 (i.e., tetrakis(triphenylphosphine)palladium), palladium chloride, palladium acetate, or at least one of CuI.

[0035] According to a preferred embodiment of the present invention, the solvent includes at least one of N,N-dimethylformamide, benzene, acetone or ethanol.

[0036] According to a preferred embodiment of the present invention, the protective gas atmosphere includes nitrogen or a rare gas.

[0037] According to a preferred embodiment of the present invention, a washing step is further performed after the Stille coupling reaction is completed; the washing reagent is preferably a sodium chloride solution; after the washing, a chromatographic separation and purification step is further performed; the chromatographic separation and purification preferably uses a silica gel column.

[0038] The third aspect of the present invention provides a polymer, wherein the monomer of the polymer is the thienylquinoxaline compound described in the first aspect of the present invention; the polymer has a structure shown in formula (II):

[0039]

[0040] A polymer provided according to an embodiment of the present invention has at least the following beneficial effects:

[0041] (1) The polymer of the present invention uses 2,3-di(thiophene-2-yl)quinoxaline as an acceptor, thiophene or 3,4-ethylenedioxythiophene (EDOT) as a π bridge, and thiophene derivatives as donors to form a D-π-A-π-D structure. 2,3-Di(thiophene-2-yl)quinoxaline has a strong electron-withdrawing ability and can enhance the intramolecular charge transfer of the DAD conjugated polymer. EDOT, as a strong electron-donating group, can reduce the initial oxidation potential of the monomer, reduce the optical band gap of the conjugated polymer, and improve the electrochromic performance.

[0042] (2) Under the action of an applied voltage, the polymer of the present invention can be observed to undergo a stable and reversible color change from brown-green to emerald green, or brown-yellow to gray, and has good electrochromic properties such as high contrast, high coloring efficiency, and fast switching time.

[0043] According to a preferred embodiment of the present invention, R 1 , R 2 , R 3 and R 4 Independently selected from C 4~15 Alkyl, C 6~20 or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl.

[0044] According to a preferred embodiment of the present invention, n represents the average degree of polymerization, and n is 10-5000.

[0045] According to a preferred embodiment of the present invention, n is 10-3000.

[0046] According to a preferred embodiment of the present invention, the polymer is selected from one of the following structural formulas:

[0047]

[0048] A fourth aspect of the present invention provides a method for preparing a polymer, comprising the following steps:

[0049] The thienylquinoxaline compound described in the first aspect of the present invention is mixed with an electrolyte solution and then subjected to electrochemical polymerization reaction using a constant potential method to obtain the thienylquinoxaline compound.

[0050] According to a preferred embodiment of the present invention, the concentration of the thienylquinoxaline compound in the solvent is 1 to 12 mmol·L -1 .

[0051] According to a preferred embodiment of the present invention, the concentration of the thienylquinoxaline compound in the solvent is 1 to 10 mmol·L -1 .

[0052] According to a preferred embodiment of the present invention, the concentration of the electrolyte solution is 0.05-0.3 mol·L -1 .

[0053] According to a preferred embodiment of the present invention, the concentration of the electrolyte solution is 0.06-0.1 mol·L -1 .

[0054] According to a preferred embodiment of the present invention, the electrochemical polymerization reaction adopts a three-electrode system, wherein an Ag / AgCl electrode is used as a reference electrode, a platinum wire is used as a counter electrode, and a Pt / ITO conductive glass is used as a working electrode.

[0055] According to a preferred embodiment of the present invention, the organic solvent is at least one of dichloromethane, chloroform or acetonitrile.

[0056] According to a preferred embodiment of the present invention, the electrolyte in the electrolyte solution is at least one of tetrabutylammonium hexafluorophosphate, tetrabutylammonium tetrafluoroborate or lithium perchlorate.

[0057] The fifth aspect of the present invention provides an electrochromic material, comprising the polymer described in the third aspect of the present invention.

[0058] The sixth aspect of the present invention provides an electrochromic device, comprising the polymer described in the third aspect of the present invention or the electrochromic material described in the fifth aspect of the present invention.

[0059] According to a preferred embodiment of the present invention, the electrochromic device includes at least one of a display, an electrochromic glass, a smart window or a rearview mirror.

[0060] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be obvious from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0062] Figure 1This is the spectroelectrochemical diagram of the polymer in the MeCN-Bu4NPF6 (0.1 mol / L) system.

[0063] Figure 2 This is the permeability-time curve of the polymer in the MeCN-Bu4NPF6 (0.1 mol / L) system.

[0064] Figure 3 This is the short-term memory effect of the polymer in the MeCN-Bu4NPF6 (0.1 mol / L) system. DETAILED DESCRIPTION

[0065] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0066] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0067] Example 1

[0068] This example provides a thienylquinoxaline compound I-1, the reaction equation and preparation method thereof are as follows:

[0069]

[0070] Under nitrogen atmosphere, 5,8-bis(5-bromothiophen-2-yl)-2,3-bis(5-chloro-4-octylthiophene-2-yl)-6,7-difluoroquinoxaline (0.14 g, 0.148 mmol), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (0.1 g, excess), and catalyst Pd(PPh 3 ) 4 (0.017g, 0.0148mmol) was placed in a 250mL single-necked flask, toluene (32mL) and N, N-dimethylformamide (8mL) were added and stirred evenly, and heated to 120°C for condensation and reflux reaction for 48 hours. After the system was cooled, the product was poured into saturated brine, extracted with dichloromethane 4 to 5 times, and then a small amount of water was added to wash the organic layer, and then the solvent was removed by reduced pressure distillation and rotary evaporation, and separated by silica gel chromatography column, the eluent was (DCM: PE = 1: 5), and the product was purified to obtain 34.2mg of black powder with a yield of 21.6%.

[0071] The H NMR spectrum data of the product are: 1H NMR(400MHz,Chloroform-d)δ7.57(d,J=4.0Hz,2H),7.17(s,2H),7.00(d,J=4.1Hz,2H),6.13(s,2H),4.21(d ,J=53.1Hz,8H),2.42(t,J=7.8Hz,4H),1.42(q,J=7.4Hz,4H),1.21(d,J=12.9Hz,24H),0.80(t,J=6.7Hz,6H).

[0072] Example 2

[0073] This example provides a thienylquinoxaline compound I-2, the reaction equation and preparation method thereof are as follows:

[0074]

[0075] Under nitrogen atmosphere, 5,8-bis(5-bromothiophene-2-yl)-2,3-bis(4-chloro-5-(2-ethylhexyl)thiophene-2-yl)-6,7-difluoroquinoxaline (0.07 g, 0.074 mmol), tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane (0.076 g, 0.178 mmol), and catalyst Pd(PPh3)4 (0.0086 g, 0.0074 mmol) were placed in a 250 mL single-necked flask, TOL (32 mL) and DMF (8 mL) were added and stirred evenly, and the mixture was heated to 120°C and refluxed for 48 hours. After the system was cooled, the product was poured into saturated brine and extracted with dichloromethane for 4 to 5 times. A small amount of water was added to wash the organic layer. The solvent was then removed by reduced pressure distillation and rotary evaporation. The product was separated by a silica gel chromatography column with an eluent of (DCM: PE = 1: 5). Purification gave 15.7 mg of a purple-black powdery product with a yield of 19.86%.

[0076] The H NMR spectrum data of the product are: 1 H NMR(400MHz,Chloroform-d)δ7.86(d,J=4.1Hz,2H),7.40(s,2H),7.29(d,J=4.1Hz,2H),6.21(s,2H),4.27(d,J =35.0Hz,8H),2.74(d,J=7.1Hz,4H),1.71(q,J=6.1Hz,2H),1.24(dd,J=24.6,19.8Hz,20H),1.00–0.65(m,15H).

[0077] Example 3

[0078] This example provides a polymer II-1, whose reaction equation and preparation method are as follows:

[0079]

[0080] Electrochemical polymerization was carried out in a one-chamber three-electrode system, with the working electrode being ITO conductive glass, the counter electrode being a platinum sheet, and the reference electrode being an Ag / AgCl electrode (AgCl coating was generated on the surface of the silver wire by electrolysis in a 6 mol / L HCl solution at a constant potential of 1.5 V for 100 s).

[0081] Using 10 mL of refined dichloromethane as the electrolyte, the thienylquinoxaline compound I-1 (0.01 mol / L) prepared in Example 1 as the polymerization monomer, and tetrabutylphosphine hexafluoride (0.1 mol / L) as the electrolyte, the polymerization was carried out by constant potential method, the polymerization potential was 0.75 V, the polymerization time was 30 s, and the polymer film obtained by electrodeposition was rinsed with acetonitrile.

[0082] (1) Study on electrochromic properties

[0083] The prepared polymer film II-1 deposited on the ITO conductive glass was placed in a three-electrode electrolytic cell containing a 0.1 mol / L tetrabutylphosphine hexafluoride dichloromethane solution, wherein the working electrode was the ITO conductive glass with the polymer film II-1 attached, the counter electrode was a platinum sheet, and the reference electrode was an Ag / AgCl electrode. The voltage applied to the working electrode was adjusted by an electrochemical workstation using a constant potential method, and a UV-visible spectrometer was used to record the changing trend of the absorption spectrum of the polymer II-1 at different voltages, thereby obtaining the spectral electrochemical spectrum of the polymer.

[0084] The spectroelectrochemical diagram of the test polymer II-1 in the MeCN-Bu4NPF6 (0.1 mol / L) system is as follows: Figure 1 As shown in (a), combined with the color change of the polymer material observed with the naked eye, it can be seen that with the increase of the potential, the color of the polymer material changes from brown-green to emerald green (brown-green in the completely dedoped state). This is because the neutral polymer material has an absorption peak in the cyan region and the red region respectively, and the color of the neutral polymer material appears as brown-green; after the polymer material is oxidized, the absorption peaks in the cyan region and the red region gradually weaken, and finally disappear completely, the absorption peak in the near-infrared region appears and gradually rises, and the color also changes to emerald green.

[0085] (2) Use a UV-visible spectrophotometer to measure the transmittance of the polymer film in the doped state and the neutral state at a specific wavelength under a square wave potential, so as to calculate the optical contrast, response time, etc.; the UV-visible spectrophotometer records the time-transmittance curve, and the electrochemical workstation records the time-current curve. Based on these two curves, the coloring efficiency can also be calculated.

[0086] The transmittance-time curves of polymer II-1 at 1100nm, 890nm, 700nm and 472nm were tested. The response time and coloring efficiency calculated from the time-transmittance curve are shown in Table 1. As can be seen from Table 1, polymer II-1 has a fast response time and a high coloring efficiency.

[0087] Table 1 Electrochromic parameters

[0088]

[0089] The optical transmittance of polymer II-1 was studied by timed absorption method at wavelengths of 1100nm, 890nm, 700nm and 472nm. During the experiment, the time interval of the potential step change was 5s. Figure 2 (a) As shown. At four wavelengths, polymer II-1 exhibits a certain optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of the polymer material, and polymer II-1 can change from brown-green in the completely dedoped state to emerald green in the doped state.

[0090] Using the constant potential method, a voltage was applied to the working electrode for 10 s and for 2 s every 100 s via an electrochemical workstation. At the same time, a UV-visible spectrometer was used to record the changing trends of the transmittance of the oxidized and reduced states of the polymer at the maximum absorption peak, thus obtaining the short-term memory effect spectrum of the polymer.

[0091] The short-term memory effect of polymer II-1 was tested at a wavelength of 1100 nm. Voltages of -0.2 V and 1.0 V were applied, and the transmittance changes of the polymer in the neutral state and the doped state were recorded. Figure 3 As shown in (a), it was found that the transmittance change of polymer II-1 in the neutral state was 2.25%, and the transmittance change in the doped state was 1.33%, which indicates that polymer II-1 has excellent short-term memory effect.

[0092] Example 4

[0093] This example provides a polymer II-2, whose reaction equation and preparation method are as follows:

[0094]

[0095] Electrochemical polymerization was carried out in a one-chamber three-electrode system, with the working electrode being ITO conductive glass, the counter electrode being a platinum sheet, and the reference electrode being an Ag / AgCl electrode (AgCl coating was generated on the surface of the silver wire by electrolysis in a 6 mol / L HCl solution at a constant potential of 1.5 V for 100 s).

[0096] 10 mL of refined dichloromethane was used as the electrolyte, the thienylquinoxaline compound I-2 (0.01 mol / L) prepared in Example 2 was used as the polymerization monomer, and tetrabutylphosphine hexafluoride (0.1 mol / L) was used as the electrolyte. The polymerization was carried out by constant potential method, the polymerization potential was 0.85 V, the polymerization time was 35 s, and the polymer film obtained by electrodeposition was rinsed with acetonitrile.

[0097] Electrochromic performance research

[0098] (1) The spectroelectrochemical diagram of polymer II-2 in MeCN-Bu4NPF6 (0.1 mol / L) system is as follows: Figure 1 As shown in (b), combined with the color change of the polymer material observed with the naked eye, it can be seen that with the increase of the potential, the color of the polymer material changes from brown to gray (brown in the completely dedoped state). This is because the neutral polymer material has an absorption peak in the cyan region and the red region respectively, and the color of the neutral polymer material appears as brown. After the polymer material is oxidized, the absorption peaks in the cyan region and the red region gradually weaken and finally disappear completely, and the absorption peak in the near-infrared region appears and gradually rises, and the color also changes to gray.

[0099] (2) The transmittance-time curves of polymer II-2 at 1100nm, 935nm, 715nm and 475nm were tested. The response time and coloring efficiency calculated from the time-transmittance curves are shown in Table 2. As can be seen from Table 2, polymer II-2 has a higher optical contrast and a higher coloring efficiency.

[0100] Table 2 Electrochromic parameters of polymer II-2

[0101]

[0102] The optical transmittance of polymer II-2 was studied by timed absorption method at wavelengths of 1100nm, 935nm, 715nm and 475nm. During the experiment, the time interval of the potential step change was 5s. Figure 2 (b) As shown. At three wavelengths, polymer II-2 exhibits good optical contrast and good optical stability; in addition, the optical transmittance has a great influence on the color change of polymer II-2, and polymer II-2 can change from brown-yellow in the completely dedoped state to gray in the doped state.

[0103] (3) The short-term memory effect of polymer II-2 was tested at a wavelength of 1100 nm. Voltages of -0.3 V and 1.1 V were applied, respectively, and the transmittance changes of polymer II-2 in the neutral state and the doped state were recorded. Figure 3As shown in (b), it was found that the transmittance change of polymer II-2 in the neutral state was 3.49%, and the transmittance change in the doped state was 0.56%, which indicates that polymer II-2 has a good short-term memory effect.

[0104] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

Claims

1. A thienylquinoxaline compound, characterized in that: It has the structural formula shown in formula (I): Wherein, R1, R2, R3 and R4 are independently selected from halogen, C 1~18 Alkyl, C 6~20 or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl; X1 and X2 are independently selected from halogen; π is selected from thiophene or 3,4-ethylenedioxythiophene; D is selected from thiophene or 3,4-ethylenedioxythiophene.

2. The thienylquinoxaline compound according to claim 1, characterized in that: R1, R2, R3 and R4 are independently selected from C 4~15 Alkyl, C 6~20 or aryl substituted by halogen, nitro, amino, hydroxyl or carboxyl.

3. The thienylquinoxaline compound according to claim 1 or 2, characterized in that: The thienylquinoxaline compound is selected from one of the following structural formulas:

4. The method for preparing a thienylquinoxaline compound according to any one of claims 1 to 3, characterized in that: The steps include: Under a protective gas atmosphere, the receptor, compound 1, a solvent and a catalyst are mixed to carry out a Stille coupling reaction to obtain a thienylquinoxaline compound; The compound 1 is selected from tributyl(2,3-dihydro[3,4-b][1,4]dioxin-5-yl)stannane or tributyl(2-thienyl)tin; The structural formula of the receptor is as follows:

5. The preparation method according to claim 4, characterized in that: The mass ratio of the receptor to compound 1 is 1:(1-5); Preferably, the mass ratio of the acceptor to the catalyst is 1:(0.03-0.0625).

6. The preparation method according to claim 4, characterized in that: The temperature of the Stille coupling reaction is 70-130°C.

7. A polymer, characterized in that The monomer of the polymer is the thienylquinoxaline compound according to any one of claims 1 to 3; the polymer has a structure shown in formula (II):

8. The method for preparing a polymer according to claim 7, characterized in that: The steps include: The thienylquinoxaline compound according to any one of claims 1 to 3, an organic solvent and an electrolyte solution are mixed and then obtained by electrochemical polymerization reaction using a constant potential method.

9. An electrochromic material, characterized in that: Comprising the polymer described in claim 7.

10. An electrochromic device, characterized in that: Comprising the polymer according to claim 7 or the electrochromic material according to claim 9.

Citation Information

Patent Citations

  • Copolymer and organic photovoltaic element

    CN113061235A

  • Cathode interface layer material, cathode interface layer coating liquid and organic photovoltaic module

    CN117050303A

  • Preparation method of polymer photovoltaic material

    CN117757044A